The Methodology of Functioning Engineering Mechanisms in the System of Auditing Controls - Moskvitin, Evgenij Ju.; Sherbakova, Oksana A.; Sverchkova, Ol'ga F.; Marjanova, Svetlana A.; Bykadorov, Viktor V. (International Journal of Economics and Financial Issues, 2016)
In connection with the crisis increases the relevance of audit control in the Russian economy. Great influence on the modern accounting in Russia have been successfully carried out reforms and existing engineering mechanisms in the system of auditing controls. The article shows the different interpretations of the concept of “engineering”, and discusses the methodology, methods and mechanisms of functioning of engineering mechanisms in the system audit trail, as well as the main directions of the use of accounting and auditing engineering and basic engineering of accounting tools of various kinds. Model instruments and statutory audit of engineering are used in a variety of processes, not only at the micro level, but also at the meso and macro levels. The article identified and grouped the main problems of further development of Russian accounting and reporting. Showing difficulties that do not allow to apply international auditing standards in full, as well as proposed solutions to these problems. As one of these solutions to the identified problems proposed accounting model for using engineering mechanisms in the audit. Keywords: Audit, Accounting, Engineering JEL Classifications: A20; L11